Open Source Software Development Should Strive for EVEN GREATER CODE MAINTAINABILITY. - Sarnoladas, Ioannis; Stamelos, Ioannis; Angelis, Lefteris; Oikonomou, Apostolos (Communications of the ACM, 2004)
This article focuses on the development of open source software (OSS). OSS, a term first coined in 1998, has spurred many products in its short history, most notably the Linux operating system, the Apache server, and the so-called killer-apps such as BIND and Sendmail. Unlike the traditional closed source software (CSS), OSS can be freely used, modified, and redistributed. Its source code is also freely accessible. Today, it is common to find CSS projects evolve into OSS in order to obtain its benefits. Occasionally, OSS projects become CSS, but usually for different reasons. OSS development emphasizes the maintainability of the software released. Making software available on the Internet allows developers around the world to contribute code, adding new functionality, improving the present one, and submitting bug fixes to the current release. The measurement of source code provides useful information for the assessment of its quality, predicting to some extent the external system quality characteristics, such as maintainability, reliability, extensibility, and portability.